Wicked. For good [videorecording (DVD)] - Holzman, Winnie; Fox, Dana; Grande, Ariana; Erivo, Cynthia, 1987-; Bailey, Jonathan, 1988-; Slater, Ethan, 1992-; Yang, Bowen, 1990-; Bode, Marissa, 2000-; Yeoh, Michelle, 1962-; Goldblum, Jeff, 1952-; Brooks, Alice, 1979-; Tazewell, Paul; et al. (Universal Studios, 2026)
"Elphaba and Glinda are now estranged, each living with the consequences of their choices. Elphaba, now demonized as The Wicked Witch of the West, lives in exile, continuing her fight to expose The Wizard. Meanwhile, Glinda has become a glamorous symbol of Goodness, basking in the perks of fame and popularity. As the angry citizens of Oz rise up against the Wicked Witch, Glinda and Elphaba must reunite and truly see each other--if they are to change themselves, and all of Oz."--